Black-Scholes Formula for Asian Option with Several Futures - Alaei, Mohammad Ebrahim (Armenian Journal of Mathematics, 2017)
The paper suggests the Black-Scholes type formulas for some options. The Asian options for several futures with depending components and uniform time steps are investigated.